1999
DOI: 10.1007/bf02482295
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated brief episodes of ischemia and reperfusion in isolated perfused rat hearts

Abstract: The effects of ischemia and reperfusion on the coronary endothelium and myocardium as well as tolerance to ischemia/reperfusion injury were assessed using isolated retrogradely perfused rat hearts. Repeated brief episodes of myocardial ischemia followed by reperfusion is known to have a protective effect against subsequent myocardial infarction. However, no studies have been performed with perfusion in the absence of blood cells to determine the effect of repeated ischemia and reperfusion on the coronary endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…For example, in hemodialysis patients, repeated demand ischemic episodes during hemodialysis result in regional wall motion abnormality at rest because of myocardial hibernation and fibrosis . Moreover, it has been shown that repeated brief episodes of ischemia, followed by reperfusion, can beget myocardial damage when the ischemic period exceeds the presumptive threshold …”
Section: Discussionmentioning
confidence: 99%
“…For example, in hemodialysis patients, repeated demand ischemic episodes during hemodialysis result in regional wall motion abnormality at rest because of myocardial hibernation and fibrosis . Moreover, it has been shown that repeated brief episodes of ischemia, followed by reperfusion, can beget myocardial damage when the ischemic period exceeds the presumptive threshold …”
Section: Discussionmentioning
confidence: 99%